The New Child Health Insurance Expansions How Will School-Based Health Centers Fit In? - Koppelman, Jane.; Lear, Julia Graham; George Washington Univ., Washington, DC. School of Public Health and Health Services ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
Under the State Child Health Insurance Program, states receive funds to purchase health insurance for low-income, uninsured children. Noting that partnering with managed care will be essential if school-based health centers are to receive reimbursement for serving the publicly insured portion of their clientele, this paper examines the relationship between this public insurance program and school-based health centers (SBHCs). The paper first describes the establishment of SBHCs in the early 1970s and their expansion, focusing on the financing mechanisms used. The paper then describes the State Child Health Insurance Program, including the views of federal and state agencies, health plans, and local SBHCs on the challenges of developing contracts, the incentives and disincentives health plans have to contract with SBHCs, and what has accounted for success where relationships are moving forward. Finally, the paper presents case studies on the experiences of Colorado and Connecticut in addressing these evolving issues. (KB)
Sponsoring Agency: Robert Wood Johnson Foundation, Princeton, NJ.
ERIC Note: Paper presented at the Annual Conference of the National Association School-Based Health Care (Los Angeles, CA, June 25, 1998).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Health; Comprehensive School Health Education; Elementary Secondary Education; Health Insurance; School Health Services; State Action; State Federal Aid; State Programs; Childrens Health Insurance Program -- Colorado -- Connecticut -- School Based Health Clinics; Reports, Descriptive; Speeches/Meeting Papers